Analysis of Service Quality Measurement at Vocational Higher Education with the Higher Education Performance Method (HEdPERF) and Importance Performance Analysis (IPA) - Tita Latifah Ahmad; Sherly Ayu Wardhani (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Higher Education Institutions (HEIs) need to possess and maintain a competitive advantage to effectively compete with other HEIs, and one of the ways to achieve this is by providing quality services. This study aims to measure service quality at Vocational Higher Education using the HEdPERF framework. The researchers add an indicator regarding an important aspect of vocational education. That is the alignment of the skills acquired by students during their internship with the actual job obtained, as a difference with other studies. The data analysis uses the IPA method. Out of the 47 indicators of service quality, there are 5 indicators in Quadrant A (Concentrate here) which are top priorities in formulating improvement strategies that consist of Teachers' Profile (Communication Skill) factors, Management Support factors (Safety Equipment and Administrative Work) and Facilities factors (Supporting Facilities). There are 24 indicators in Quadrant B (Keep Up The Good Work), 8 indicators in Quadrant C (Low Priority), and 10 indicators in Quadrant D (Possible Overkill). Some of the recommended improvement strategies are implementing lecturer creativity in learning, increasing lecturers competence in teaching communication, providing fast and easy administrative services, organizing safety training, reducing class capacity, renovating buildings, completing class needs, and doing routine chair maintenance.